(untitled) (AYUSHDHARA, 2017)
Basti Chikitsa regarded as the prime treatment modality among the Panchakarma. It is having not only curative action but also preventive and promotive actions. Basti therapy is considered as Chikitsardha among all therapy and some physician recognize it as complete therapy because Basti has a vast field of therapeutic action. Basti is not merely the enema; rather it is a highly complex, sophisticated, and systemic therapy having wider range of therapeutic actions and indications. It is considered as prime treatment modality for Vata Dosha. Yapana Basti is a subtype of Asthapana Basti, which is having the property to support life and promote longevity and widely used in various disorders such as Pakshaaghata, Siragata Vata, Snayugata Vata, Mamsagata Vata, Asthigata Vata, Majjagta Vata, Shukragata Vata, Sarvanga Vata and Ekangavata. Yapana Basti can be administered at OPD level without any specific restrictions, and hence it can be considered as an ideal therapeutic modification of Basti therapy for the present life style. Yapana Basti and Madhutailika Basti are regarded as one and same, so in this article both are discussed separately. Here, an effort has made to compile and critically analyse the principles, concepts and practices by referring the Brihatrayi, Laghutrayis, commentaires and current researches.